Cerebral oxygenation during skin-to-skin care in preterm infants not receiving respiratory support. Issue 2 (26th July 2017) - Lorenz, Laila; Marulli, Adriana; Dawson, Jennifer A; Owen, Louise S; Manley, Brett J; Donath, Susan M; Davis, Peter G; Kamlin, C Omar F
Abstract : Objective: Skin-to-skin care (SSC) has proven benefits in preterm infants, but increased hypoxic and bradycardic events have been reported. This may make clinicians hesitant to recommend SSC as standard care. We hypothesised that regional cerebral oxygenation (rStO2 ) measured with near infrared spectroscopy is not worse during SSC compared with standard incubator care. Design: Prospective, observational, non-inferiority study. Setting: Single tertiary perinatal centre in Australia. Patients: Forty preterm infants (median (IQR) 30.6 (29.1–31.7) weeks' gestation) not receiving respiratory support were studied on day 14 (8–38). Interventions: Recordings during 90 min of incubator care, followed by 90 min of SSC. Each infant acted as their own control and caregivers were blinded to the rStO2 measurements. Main outcome measures: The primary outcome was the mean difference in rStO2 between SSC and incubator care. The prespecified margin of non-inferiority was −1.5%. Secondary outcomes included heart rate (HR), peripheral oxygen saturation (SpO2 ), time in quiet sleep, temperature and hypoxic (SpO2 <80% for >5 s) or bradycardic events (HR <80 bpm for >5 s) and time spent in cerebral hypoxia (rStO2 <55%) and hyperoxia (rStO2 >85%). Results: Mean (SD) rStO2 was lower during SSC compared with incubator care: 73.6 (6.0)% vs 74.8 (4.6)%, mean difference (95% CI) 1.3 (2.2 to 0.4)%. HR was 5 bpm higher, SpO2 1% lower and time in quiet sleep 24% longer during SSC. Little evidence of a difference was observed in temperature. The number of hypoxic or bradycardic events as well as the proportion of time spent in cerebral hypoxia and hyperoxia was very low in both periods. Conclusions: Mean rStO2 was marginally lower during SSC without observed differences in hypoxic or bardycardic events but an increase in time spent in quiet sleep. Trial registration number: This trial is linked to Australian New Zealand Clinical Trials Registry: identifier 12616000240448. It was registered pre-results.